THE OBJECTIVE OF ISLAMIC BANK: A CASE STUDY IN SURAKARTA REGION - Ibrahim Fatwa Wijaya (University of Merdeka Malang, 2014)
The purposes of this research were for exploring the perception of the Islamic Banking stakeholders relatedwith the objective of Islamic Banking that operated in the dual banking system, Indonesia and for measuringthe gap between the perception and expectation of the stakeholders toward the objective of Islamic bank. Theprimary data was collected by questionnaires. The Respondents were limited only in the Surakarta region.They were customers, lecturers, students, employees, bank managers, regulators, and ulama (Moslem religiousteachers). Factor analysis was conducted for grouping or classifying the variables into the same group whichhad the same characters while Kruskall Wallis test was used for examining the different perception among thestakeholders. At last, paired sample t-test was used to measure the gap between perception and expectationamong the stakeholders. The findings of this study were first, stakeholders concluded that social objective ofIslamic was more important than the commercial one; second, there was a significant different perception on theIslamic Banking objective among the stakeholders; and third, there was a gap between the perception andexpectation of the stakeholders about Islamic Banking objectives.